(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The article is devoted to the problem of the methodology formation of the study of literature for children and youth in the Ukrainian literary criticism. Margarita Slavova presents four main approaches to the theory of children’s literature: pedagogical, psychological, literature analysis for children in the context of receptive aesthetics and cultural studies. The article deals with philological and other critical approaches (naratology, receptive-aesthetic, comparative), which Ukrainian literary scholars practiced in scientific researches. The literary, didactic and multidisciplinary interpretation strategies and the effectiveness of their tools in the study of artistic texts for children and young people are described by the author in detail.